2007
DOI: 10.3844/ajabssp.2007.15.22
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Capital on Adoption of Rural Development Programs by Farmers in the Caspian Sea Region of Iran

Abstract: The main purpose of this study was to measure social capital (consisting of structural and cognitive) of mainly rice producing farmers in the Caspian See region of Iran. The secondary purpose was to determine the influence of farmers' social capital on adoption of Rural Development Programs (RDPs). This was a descriptive-correlation and a causal-comparative survey study. The population of this study consisted of 5746 farmers and by a stratified proportional random sampling technique, 396 farmers were cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It is a product of social (multi-agent) interaction (Yiheyis et al 2007). Therefore, these social capital variables could act as important predicting factors in determining the adoption and utilisation of RDPs programs (Firouzjaie et al 2007) in an efficient way. As can be seen in Table 1, both the IPFs and the LAGs involve local stakeholders and represent the legal instruments capable of aggregation at the local level, but are especially useful in defining and developing the social capital of a given geographical area or production system.…”
Section: The Territorial Social Capital and The Analysis Of Stakehold...mentioning
confidence: 99%
“…It is a product of social (multi-agent) interaction (Yiheyis et al 2007). Therefore, these social capital variables could act as important predicting factors in determining the adoption and utilisation of RDPs programs (Firouzjaie et al 2007) in an efficient way. As can be seen in Table 1, both the IPFs and the LAGs involve local stakeholders and represent the legal instruments capable of aggregation at the local level, but are especially useful in defining and developing the social capital of a given geographical area or production system.…”
Section: The Territorial Social Capital and The Analysis Of Stakehold...mentioning
confidence: 99%
“…All of them have indicated that they are involved in the poverty program over the past 10 years since year 2000. Data were gathered through in-depth interviews with the informants over a period of six months, focusing on the informant's perception of self, life and experience and expressed in his/her own words about the way they understanding the concept of participation and empowerment in community development (Panahi and Malekmohammadi, 2010;Firouzjaie et al, 2007;Ahmed et al, 2011;Mok et al, 2007). Each interview lasted for about one to two hours, depending on the situation.…”
Section: Data Collectionmentioning
confidence: 99%